Usos e noções do hipertexto no ambiente virtual de aprendizagem: análise a partir da visão dos professores conteudistas que atuam na educação superior - Silva, Luciana da (2013)
This study examined the habits and notions of hypertext from the perspective of teachers who work in specialization course Media in Education, held in virtual learning environment (VLE) in the context of a university participant System Open University of Brazil (UAB). The qualitative research was conducted through a literature search, a questionnaire and an interview. With the interpretive content analysis of the data obtained through these instruments was found with teachers notions and practices that have in relation to writing and reading hypertext which constitutes learning object. According to the Benchmarks of Quality Distance Education MEC, is that the content-professional with a multidisciplinary team is responsible for the content of the proposed virtual classroom discipline course in distance education mode. It is the relationship between education and communication which sought to analyze the use of hypertext as an interface for searching and for building collaborative knowledge. We tried to discuss the content or pedagogy sustained in content by Paulo Freire. Examined whether this exists in virtual education pedagogy to think the pedagogical use of hypertext in this new type of education, this systematic study, which aims to contribute to this area of knowledge.